Ruin probability in a risk model with variable premium intensity and risky investments - Mišura, Ûliâ Stepanovna; Perestûk, Nikolaj Alekseevič; Ragulìna, Olena Ûrìïvna (My University, 2015)
We consider a generalization of the classical risk model when the premium intensity depends on the current surplus of an insurance company. All surplus is invested in the risky asset, the price of which follows a geometric Brownian motion. We get an exponential bound for the infinite-horizon ruin probability. To this end, we allow the surplus process to explode and investigate the question concerning the probability of explosion of the surplus process between claim arrivals.
Opuscula Mathematica
Keywords: risk process; infinite-horizon ruin probability; variable premium intensity; risky investments; exponential bound; stochastic differential equation; explosion time; existence and uniqueness theorem; supermartingale property